Evaluation of the usability of various rapid antibody tests in the diagnostic application for COVID-19. (May 2021) - Uwamino, Yoshifumi; Wakui, Masatoshi; Aoki, Wataru; Kurafuji, Toshinobu; Yanagita, Emmy; Morita, Maasa; Nagata, Mika; Inose, Rika; Noguchi, Masayo; Yokota, Hiromitsu; Hasegawa, Naoki; Saya, Hideyuki; et al.
Background: The usability of laboratory tests related to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is critically important for the world undergoing the COVID-19 pandemic. The present study aimed to assess the diagnostic usability of rapid tests for the detection of antibody against SARS-CoV-2 through comparison of their results with the results of reverse transcription polymerase chain reaction (RT-PCR) test for the detection of SARS-CoV-2 genomic RNA and with the results of a quantitative test for antibody detection. Methods: Serum samples were collected from 18 patients undergoing RT-PCR testing for SARS-CoV-2. Twelve patients were RT-PCR positive while six were negative. A quantitative test based on chemiluminescent immunoassay and three rapid tests based on immunochromatography were performed to detect anti-SARS-CoV-2 IgG and IgM. Results: All the antibody tests exhibited poor sensitivity at the timing of initial RT-PCR diagnosis. IgG responses occurring prior to or simultaneously with IgM responses were observed through not only the quantitative test but also the three rapid tests. Based on concordance with the quantitative test results, the large variance among the three rapid tests was revealed. Conclusions: All antibody tests were unsatisfactory to replace RT-PCR for the early diagnosis of COVID-19. Rapid antibody tests as well as a quantitative antibody test were useful in the assessment of immune responses in COVID-19. The obvious variance among the three rapid tests suggested limited accuracy and difficult standardization. Diagnostic usability of rapid antibody tests for COVID-19 should be investigated rigorously.